Behavioral Intention to Adopt Digital Library by the Undergraduates. Issue 2 (3rd April 2019) - Moorthy, Krishna; Chun T'ing, Loh; Ming, Kiing Siew; Ping, Chiong Chui; Ping, Ler Yu; Joe, Lim Qiao; Jie, Wong Ying
ABSTRACT: The purpose of this research is to investigate the factors that affect undergraduates' behavioral intention to use digital library among the private universities in Malaysia. The target respondents are undergraduates from Malaysian private universities. Questionnaires were distributed among 500 undergraduates through either online or face-to-face method. Reliability test, normality test, Pearson Correlation Coefficient analysis, and Multiple Linear Regression (MLR) were carried out for data analysis. Performance expectancy, social influence, facilitating conditions, hedonic motivation, habit, and information quality had a positive and significant association with behavioral intention to adopt a digital library except for effort expectancy. This research successfully reinforced that the inspiration to ameliorate Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) by synthesis of Information Systems Success Model (ISSM). This proposed framework with a combination of ISSM and UTAUT 2 has enhanced the fitness of UTAUT 2. Universities that have yet to implement digital library can comprehend undergraduates' needs better by considering all the significant factors to develop a digital library. The universities with the digital library may also notice the important features of the existing digital library that should be maintained and upgraded constantly so that they can fulfil undergraduates' requirements.